PENGARUH PROMOSI DAN BRAND AWARENESS TERHADAP KEPUTUSAN PEMBELIAN PRODUK AQUA - Steven Steven; Angelina Fitria Rina Sari Fitria Rina Sari (Jurnal Ekonomi Integra, 2019)
The success of a company in terms of product quality can be seen and judged also by the company's brand awareness about the product, attractive brand awareness of course can attract prospective buyers or retain existing buyers, of course all that must also be supported by good promotion interesting. Brand awareness and promotion (advertising) of a company for its products can of course influence the purchasing decisions of consumers or prospective consumers themselves. This certainly has a positive impact on the company in the long term. This study wants to prove the influence of each variable, namely brand awareness and promotion of purchasing decisions, where brand awareness is an intervening variable for purchasing decisions on AQUA brand beverage products. Based on previous research and related to supporting theories proposed by experts using the SPSS program as a statistical data processing tool. This type of research is associative research. Associative research is a method / form of research carried out to connect one variable to another variable. In this study researchers used nonprobability sampling techniques because researchers did not know the total number of members of the population studied. While the sampling technique used in this study is accidental sampling, which is a form of sampling based on coincidence where, who met with the researcher and considered suitable to be a source of data that will be the sample of this study. While the sample population is 100 people, with data analysis techniques using Path Analysis Based on data processing using path analysis, it is evident that there is a significant effect of advertising and brand awareness on buying decisions and advertising variables directly affect brand awareness variables, whereas for buying decisions, advertising variables have an indirect influence